Examining Nepalese Forestry Governance from Gender Perspectives. Issue 3 (23rd February 2017) - Wagle, Radha; Pillay, Soma; Wright, Wendy
ABSTRACT: This article examines Nepalese forestry governance from gender perspectives. We argue that gendered institutional norms and values are associated with forest-governing institutions, such as forest bureaucracies, shaping the nature, and extent of women's involvement in decision-making processes in the Nepalese forest bureaucracy. Studies on Nepalese forestry reveal that substantial progress has been made in forming policies and initiating activities for including women in forestry governance of Nepal; however despite this, gendered dynamics create difficulties for women to enter and progress in the forestry profession, thereby creating gendered employment territories through institutional, legislative, normative, and infrastructural measures.